Manifestations and pathogenesis of the sebaceous gland aging - ZHENG Siqi; CHEN Shuqiong; ZHONG Meizhen; ZHENG Yue; HUANG Xiaowen (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2024)
Aging in the sebaceous glands typically begins on the sun-exposed areas, characterized by sebaceous gland hyperplasia and lipid dysbiosis. These changes result in dry and dull skin, alterations in the microbiota, pigmentation, and various skin diseases. Both intrinsic and extrinsic factors contribute to this process, causing dilation of sebaceous ducts, reducing lipid secretion, promoting gland proliferation, and inducing inflammation. Key downstream mechanisms driving sebaceous gland aging include reactive oxygen species (ROS), autophagy, the Wnt signaling pathway, and mitochondrial dysfunction. Interventions such as antioxidants, probiotics, phototherapy, and exosomes can delay the sebaceous gland aging. This article will discuss the manifestations of the sebaceous gland aging, elucidate its underlying mechanisms, review current research progress, and explore potential countermeasures.